2018
DOI: 10.32718/nvlvet8902
|View full text |Cite
|
Sign up to set email alerts
|

Features of milk productivity of cows of Ukrainian brown dairy breed and the influence of genotypical and paratypical factors on its formation

Abstract: Sklyarenko, Y.I. (2018). Features of milk productivity of cows of Ukrainian brown dairy breed and the influence of genotypical and paratypical factors on its formation. Scientific MessengerThe indicators of milk productivity of cows of Ukrainian brown dairy breed were studied. The research was carried out on the basis of breeding farms of animal breeding of this breed by assessing the data of primary zootechnical accounting. It is established that the level of milk productivity of cows meets the breed standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
(15 reference statements)
0
0
0
1
Order By: Relevance
“…However, some scientists report a more significant effect of the autumn and summer seasons of birth on the productivity [1], others [20] -about significantly higher milk yields of cows born in autumn, and some observed higher productivity in animals born in the autumn and winter seasons [16,17]. A number of authors found out that the most significant influence on the phenotypic variability of the milk productivity of first-calf heifers is caused by the "herd" factor, the year of birth is noticeably smaller, and the season of birth is the least significant [3,5,11,18,19,21].…”
Section: Ethical Approvalmentioning
confidence: 99%
“…However, some scientists report a more significant effect of the autumn and summer seasons of birth on the productivity [1], others [20] -about significantly higher milk yields of cows born in autumn, and some observed higher productivity in animals born in the autumn and winter seasons [16,17]. A number of authors found out that the most significant influence on the phenotypic variability of the milk productivity of first-calf heifers is caused by the "herd" factor, the year of birth is noticeably smaller, and the season of birth is the least significant [3,5,11,18,19,21].…”
Section: Ethical Approvalmentioning
confidence: 99%
“…Дослідження Ю. І. Скляренка зі співавторами [5,6] свідчать, що тваринам української бурої молочної породи характерні високі показники вмісту складових молока. Вміст жиру в молоці складає в ТДВ «Маяк» Сумської області 3,98 %; білка -3,55 %; казеїну -3,31 %.…”
unclassified